Índice integral para la medición del nivel de servicio de la Cooperativa Ahorro y Crédito CHONE LTDA - Peñarrieta Vélez, Emilia Guadalupe (2024)
Currently, savings and credit cooperatives seek to be competitive by providing the best quality and the best service in the market, which is why this degree work has the purpose of defining an integral index to measure the level of service of the Cooperativa de Ahorro y Crédito Chone Ltda, of the Chone canton, in order to allow the organization to identify shortcomings and thus improve the service, to finally contribute to effective decision making, for which it was necessary to define the techniques and tools among them, the SWOT matrix which allowed to identify those internal and external factors that were affecting the quality of service provided by the same, to thereby establish strategies to be evaluated and implemented within the institution. Then, the components of the service process were determined based on the integral index methodology, which required the criteria of the experts, the Delphi method and the affinity diagram, achieving through the application of these methods the selection of key service components, among them the following: Number of complaints and claims, number of customers served per day, modern equipment, service information, programs oriented to the benefit of customers and the availability of ATMs, which allowed the calculation of the Integral Index using the Saaty method, taking into account the scale of the number of customers served per day, the number of customers served per day, modern equipment, service information, programs oriented to the benefit of customers and the availability of ATMs, which allowed the calculation of the Integral Index using the Saaty method, taking into account the scale of the number of customers served per day.